Novelties in the genus Alchornea (Euphorbiaceae) - Murillo-Aldana, José (Phytotaxa, 2018)
Three new species of Alchornea from Colombia and Peru are proposed. Alchornea conceveiboides (Colombia) is characterized by abundant minute papillae on the lower surface of the blade, A. tenuinervia (Colombia) by inconspicuous higher orders of venation, and A. verticillata (Colombia, Peru) by leaves arranged in whorls of three. In addition, A. acroneura, which was previously included under A. triplinervia, is re-established, and A. valleana is excluded of Alchornea. All species are described and illustrated. Additional comments regarding their distribution are presented.